Demographic parameters related to 30-day readmission of patients with pulmonary embolism: Analysis of 650, 819 hospitalizations. (15th October 2016) - Agrawal, Yashwant; Patri, Sandeep; Chhatrala, Hardik; Joseph, Soji; Saltiel, Frank; Kalavakunta, Jagadeesh K.; Gupta, Vishal
ABSTRACT: Background: Pulmonary embolism (PE) is a serious medical condition associated with major morbidity, mortality and economic burden. Preventable hospital readmissions are a major economic challenge for the healthcare organizations and identifying patient subsets at risk of readmission will help report the issue. This retrospective study was performed to determine demographic parameters and major diagnosis linked with 30 day readmission after a PE. Methods: Nationwide Inpatient Sample (NIS) data was used to extract data of patients discharged after PE during index admission for years 2009–2013. Patients were identified by Diagnosis Related Group (DRG) number 175 and 176 which represents PE with major complications and comorbidities (MCC) and PE without MCC. Demographic parameters associated with high readmission rate were identified along with causes related to readmissions. Results: We identified a total of 650, 819 hospitalizations with PE as the index stay DRG of which 13.44% were readmitted within 30 days after hospitalizations. Patients with age > 65 years (14.05%), female (13.87%), Medicaid insurances (20.49%), low median income for zip code (15.1%) and metropolitan areas (13.71%) were associated with higher 30 day readmission rates. The most common identified cause of readmission in PE with MCC from 2009 to 2010 was heart failure (4.25%) and from 2011 to 2013 was severe sepsis (4.8%) while for PE without MCC from 2009 to 2013 was PE without MCC itself (10.24%). Conclusions: Interventions need to be directed against these set of patients and the identified causes of readmissions to reduce the rehospitalisations from PE.